The effects of head cooling on endurance and neuroendocrine responses to exercise in warm conditions - Ansley, L; Marvin, G; Sharma, A; Kendall, M.J; Jones, D. A; Bridge, M. V (Physiological research, 2008)
The present study investigated the effects of head cooling during endurance cycling on performance and the serotonergic neuroendocrine response to exercise in the heat. Subjects exercised at 75 % VO2max to volitional fatigue on a cycle ergometer at an ambient temperature of 29±1.0 °C, with a relative humidity of approximately 50 %. Head cooling resulted in a 51 % (p<0.01) improvement in exercise time to fatigue and Borg Scale ratings of perceived exertion were significantly lower throughout the exercise period with cooling (p<0.01). There were no indications of peripheral mechanisms of fatigue either with, or without, head cooling, indicating the importance of central mechanisms. Exercise in the heat caused the release of prolactin in response to the rise in rectal temperature. Head cooling largely abolished the prolactin response while having no effect on rectal temperature. Tympanic temperature and sinus skin temperature were reduced by head cooling and remained low throughout the exercise. It is suggested that there is a coordinated response to exercise involving thermoregulation, neuroendocrine secretion and behavioural adaptations that may originate in the hypothalamus or associated areas of the brain. Our results are consistent with the effects of head cooling being mediated by both direct cooling of the brain and modified cerebral artery blood flow, but an action of peripheral thermoreceptors cannot be excluded.
Keywords: Hyperthermia; svalová kontrakce; Central Fatigue; Humans; Perception; svalová únava; Skin Temperature; vysoká teplota; Muscle Contraction; Hot Temperature; Head; Oxygen Consumption; Adaptation, Physiological; Physical Endurance; mladý dospělý; dospělí; nízká teplota; financování organizované; Financing, Organized; lidé; prolaktin; Cold Temperature; časové faktory; fyzická vytrvalost; Head Cooling; hlava; Adult; kosterní svaly; Prolactin; teplota kůže; percepce; Male; Adolescent; Body Temperature Regulation; Muscle, Skeletal; spotřeba kyslíku; fyziologická adaptace; Muscle Fatigue; Young Adult; Exercise; mužské pohlaví; Time Factors; mladiství; termoregulace